A ARE PO'O TRADITION (BAMBOO NASI) AS A REPRESENTATION OF LIO TRIBE LOCAL WISDOM IN MAUTENDA VILLAGE, KAMPUNG AEGANA, WEWARIA DISTRICT, ENDE REGENCY - Anita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
The problem in this study is how the process of implementing the Are Po'o ritual, and what values ​​are contained in the Are Po'o ritual, with the aim of the study being to know the process of carrying out the Are Po'o ritual, and the value contained in the Are Po'o ritual. . the method used in this study is a qualitative research method, and is descriptive. While the data collection techniques in the form of interviews, observation and documentation. The results of the study show that the process of implementing the Are Po'o ritual goes through several stages including; Bou Mosalaki, Mendi Moke seboti, Are Sewati, and Manu Seeko, Rore Manu, Bring offerings to all three places (Pu'u Kaju Koja, Watu Pere Dhora, Tubu Dhora), Weka Wunu Muku, Ko'o Kengo Fill One Po'o, Phale Leka Nua, Mula Are. While the values ​​contained in the Are Po'o ritual include religious values, mutual cooperation values, and friendship values.